Humoral immunity response to human endogenous retroviruses K/W differentiates between amyotrophic lateral sclerosis and other neurological diseases. (14th May 2018) - Arru, G.; Mameli, G.; Deiana, G. A.; Rassu, A. L.; Piredda, R.; Sechi, E.; Caggiu, E.; Bo, M.; Nako, E.; Urso, D.; Mariotto, S.; Ferrari, S.; et al.
Abstract : Background and purpose: Human endogenous retroviruses (HERV) K/W seem to play a role in fostering and exacerbation of some neurological diseases, including amyotrophic lateral sclerosis (ALS). Given these findings, the immunity response against HERV‐K and HERV‐W envelope surface (env‐su) glycoprotein antigens in serum and cerebrospinal fluid (CSF) was investigated for ALS, multiple sclerosis (MS) and Alzheimer's disease patients and in healthy controls. Methods: Four antigenic peptides derived respectively from HERV‐K and HERV‐W env‐su proteins were studied in 21 definite or probable ALS patients, 26 possible or definite relapsing−remitting MS patients, 18 patients with Alzheimer's disease and 39 healthy controls. An indirect enzyme‐linked immunosorbent assay was set up to detect specific antibodies (Abs) against env‐su peptides. Results: Amongst the measured levels of Abs against the four different HERV‐K peptide fragments, only HERV‐K env‐su19–37 was significantly elevated in ALS compared to other groups, both in serum and CSF. Instead, amongst the Abs levels directed against the four different HERV‐W peptide fragments, only HERV‐W env‐su93–108 and HERV‐W env‐su248–262 were significantly elevated, in the serum and CSF of the MS group compared to other groups. In ALS patients, the HERV‐K env‐su19–37 Abs levels were significantly correlated with clinical measures of disease severity, both in serum and CSF. Conclusions: Increased circulating levels of Abs directed against the HERV‐W env‐su93–108 and HERV‐W env‐su248–262 peptide fragments could serve as possible biomarkers in patients with MS. Similarly, increased circulating levels of Abs directed against the HERV‐K env‐su19–37 peptide fragment could serve as a possible early novel biomarker in patients with ALS.